2016
DOI: 10.1016/j.imlet.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic features of the CD8α− dendritic cell subset in inducing functional T follicular helper cells

Abstract: T follicular helper (Tfh) cells, a true B cell helper, have a critical role in enhancing humoral immune responses. However, the initial differentiation of Tfh cells by dendritic cells (DCs), the most potent antigen presenting cells, has not been clearly understood, particularly in the knowledge of the two major conventional dendritic cell subsets, CD8α(+) DCs or CD8α(-) DCs. Here we demonstrated that the localization of CD8α(-) DCs in the marginal zone (MZ) bridging channels is closely associated with the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 33 publications
1
31
0
10
Order By: Relevance
“…Although they have been established to augment Tfh cell differentiation and antibody responses (1, 18, 38), they also support IFNγ-producing T cell responses (39, 40). Because type I IFN is most prominently induced during infections with intracellular pathogens, perhaps dispersal throughout the T cell zone allows the cDC2s to present antigen in a manner that more effectively induces a T helper 1 cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Although they have been established to augment Tfh cell differentiation and antibody responses (1, 18, 38), they also support IFNγ-producing T cell responses (39, 40). Because type I IFN is most prominently induced during infections with intracellular pathogens, perhaps dispersal throughout the T cell zone allows the cDC2s to present antigen in a manner that more effectively induces a T helper 1 cell fate.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Previously, we demonstrated that in vivo laquinimod treatment causes a disproportionate reduction in the numbers of the CD11c + CD4 + CD8α − (referred to as CD4 + ) dendritic cells (DCs). 5 The CD4 + DC subpopulation is instrumental in promoting differentiation of T follicular helper (Tfh) cells, 18 20 the CD4 + T cell subset that directs B cell differentiation, germinal center (GC) formation, and immunoglobulin (Ig) class switching. 21 Therefore, we hypothesized that laquinimod could affect several B cell activities that contribute to CNS autoimmunity.…”
mentioning
confidence: 99%
“…As DCs CD8αtambém estão presentes no baço e nos linfonodos de camundongos mas, diferentemente das DCs CD8α + , estão localizadas nas zonas marginais às células B na polpa vermelha do baço (SHIN et al, 2016). Estas células, além de serem negativas para a cadeia alfa da molécula CD8, expressam o marcador de superfície CD11b, sendo consideradas cDC2.…”
Section: Cd8α -unclassified
“…As cDCs2, por exemplo, vem sendo associadas a instrução de células Th17 enquanto que as cDCs1, principalmente as DCs CD8α + , estão relacionadas com a resposta Th1 (SCHLITZER et al, 2013;SOARES et al, 2007). Dessa forma, cada subtipo de DCs especificamente apresenta características intrínsecas a sua própria biologia que garantem a sua especialização na indução de uma polarização de células T CD4 + (SHIN et al, 2016). Essas características podem ser desde a expressão de TLRs e sua ativação frente aos seus ligantes ou, até mesmo, as expressões de diferentes moléculas co-estimulatórias, citocinas, vias de sinalização e fosforilação intracelulares e outros mecanismos dependentes do subtipo de DC (LI et al, 2016;NAPOLITANI et al, 2005;SHIN et al, 2015).…”
Section: Resposta De Celular Induzida Por Dcsunclassified
See 1 more Smart Citation